2016
DOI: 10.5114/hpr.2016.61669
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative exploration of the motivations underlying anabolic-androgenic steroid use from adolescence into adulthood

Abstract: backgroundThis study explored the direct experience of anabolic androgenic steroid (AAS) use by young men, with an emphasis on how motivations progressed from adolescent initiation to more entrenched usage. participants and procedureNine semi-structured interviews were conducted with individuals ranging in experience of AAS use, from novice to experienced users. resultsThe results indicated that the young adult men progressed through a clear transition whereby their motives for using these substances changed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 23 publications
0
14
1
1
Order By: Relevance
“…This finding supports Kanayama et al (2006) suggestion that MD may be a symptom of AAS use. For these men, it appears that AAS had created body image pathology, and it is this pathology that perpetuates their AAS use (Harris, Dunn, and Alwyn, 2016), and not the secondary reinforcers expressed by those who spoke of the positive effects of AAS use. This finding has significant implications for understanding why some men find cessation difficult despite reaching their target performance and size and why others often relapse and return to AAS use after a period of abstinence (Kirkwood, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This finding supports Kanayama et al (2006) suggestion that MD may be a symptom of AAS use. For these men, it appears that AAS had created body image pathology, and it is this pathology that perpetuates their AAS use (Harris, Dunn, and Alwyn, 2016), and not the secondary reinforcers expressed by those who spoke of the positive effects of AAS use. This finding has significant implications for understanding why some men find cessation difficult despite reaching their target performance and size and why others often relapse and return to AAS use after a period of abstinence (Kirkwood, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Recent qualitative research in the area has identified that young adult men progressed through a clear transition period whereby their motives for using AAS changed from an external desire to compete with other men within a competitive bodybuilding environment, to more internalised body image preoccupations (Harris, Dunn & Alwyn, 2016). This finding may imply an additional factor, Intrasexual competition, which may influence the decision to initiate AAS usage that has previously been overlooked.…”
Section: Intrasexual Competition and Anabolic Androgenic Steroid Usementioning
confidence: 99%
“…', to help eradicate the complications of participants who may be cycling AAS, or experiencing withdrawal. Recent qualitative research has highlight both to be common experiences of AAS users in this environment (Harris, Dunn & Alwyn, 2016).…”
Section: ) User Vs Non-usermentioning
confidence: 99%
“…Over-and underweight boys were four times more likely to use AAS than boys who perceived themselves as the right weight (Jampel et al 2016). Looking at initial and current motivations for use, Harris, Dunn, and Alwyn (2016) found that the initial external motivation of wanting to be more muscular led to an internal motivation of body image concerns. The authors concluded that continued AAS use could be linked to the development of body image disorders among young people.…”
Section: Table 1 Further Motivations For Usementioning
confidence: 96%